Molecular chaperones: guardians of the proteome in normal and disease states - Jeng, Wilson (F1000Res, 2015)
Proteins must adopt a defined three-dimensional structure in order to gain functional activity, or must they? An ever-increasing number of intrinsically disordered proteins and amyloid-forming polypeptides challenge this dogma. While molecular chaperones and proteases are traditionally associated with protein quality control inside the cell, it is now apparent that molecular chaperones not only promote protein folding in the “forward” direction by facilitating folding and preventing misfolding and aggregation, but also facilitate protein unfolding and even disaggregation resulting in the recovery of functional protein from aggregates. Here, we review our current understanding of ATP-dependent molecular chaperones that harness the energy of ATP binding and hydrolysis to fuel their chaperone functions. An emerging theme is that most of these chaperones do not work alone, but instead function together with other chaperone systems to maintain the proteome. Hence, molecular chaperones are the major component of the proteostasis network that guards and protects the proteome from damage. Furthermore, while a decline of this network is detrimental to cell and organismal health, a controlled perturbation of the proteostasis network may offer new therapeutic avenues against human diseases.